MilkyWay@home: Harnessing volunteer computers to constrain dark matter in the Milky Way. Issue Volume 9:Issue S298(2013) (6th January 2014) - Newberg, Heidi Jo; Newby, Matthew; Desell, Travis; Magdon-Ismail, Malik; Szymanski, Boleslaw; Varela, Carlos
Abstract: MilkyWay@home is a volunteer computing project that allows people from every country in the world to volunteer their otherwise idle processors to Milky Way research. Currently, more than 25, 000 people (150, 000 since November 9, 2007) contribute about half a PetaFLOPS of computing power to our project. We currently run two types of applications: one application fits the spatial density profile of tidal streams using statistical photometric parallax, and the other application finds the N -body simulation parameters that produce tidal streams that best match the measured density profile of known tidal streams. The stream fitting application is well developed and is producing published results. The Sagittarius dwarf leading tidal tail has been fit, and the algorithm is currently running on the trailing tidal tail and bifurcated pieces. We will soon have a self-consistent model for the density of the smooth component of the stellar halo and the largest tidal streams. The N -body application has been implemented for fitting dwarf galaxy progenitor properties only, and is in the testing stages. We use an Earth-Mover Distance method to measure goodness-of-fit for density of stars along the tidal stream. We will add additional spatial dimensions as well as kinematic measures in a piecemeal fashion, with the eventual goal of fitting the orbit and parameters of the Milky Way potential (and thus the density distribution of dark matter) using multiple tidal streams.